Dampak Gaji di Bawah UMR terhadap Kelayakan Hidup Karyawan UMKM - fitriani, ninis (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the impact of salaries below the Regional Minimum Wage (UMR) on the standard of living for employees working in the Micro, Small, and Medium Enterprises (MSMEs) sector. Using a qualitative descriptive approach, data were obtained through interviews, observations, and literature studies related to a decent standard of living. The results indicate that salaries below the UMR impact low purchasing power, limited access to health services, and a decreased quality of life for employees. Although MSMEs have limited capital, the mismatch between wages and a decent standard of living has the potential to reduce productivity and work motivation.